Developing a Quality Measurement Strategy in an Academic Primary Care Setting: An Environmental Scan. Issue 6 (November 2018) - Dalton, Alexandra F.; Lyon, Corey; Parnes, Bennett; Fernald, Douglas; Lewis, Carmen L.
ABSTRACT: Purpose: The purpose of this project was to: (1) develop a strategy for primary care quality measurement using an environmental scan and interviews to identify best practices and candidate measures; (2) present recommendations to facilitate successful measurement. Methods: Following stakeholder interviews and review of existing measures, we created a three-tiered recommendation system for selecting and implementing measures. We also developed a framework for reviewing and prioritizing measures and prepared a detailed project report. Results: Interviews provided a broader perspective on measuring quality, including implementing measures, measuring value, and identifying measurement gaps. Our recommendations fall into three tiers: Tier 1 measures can be implemented quickly and include clinical processes and outcomes for preventive care and disease states. Tier 2 measures require modifications to electronic health record, workflows, and/or staff preparation. Tier 3 (Strategic Vision) addresses topics that should be incorporated in the future to ensure high-quality primary care (adherence, patient activation, patient experience, teamness, staff satisfaction, and value), and infrastructure development to support ongoing quality measurement. Conclusions: Implementing a quality measurement strategy is challenging and labor-intensive but is necessary to improve healthcare quality. Our work demonstrates the effort and investment required to progress quality measurement and offers recommendations for successfully undertaking this type of endeavor.